Customer Perceptions Of The Merger Of Three Islamic Banks Into Indonesian Islamic Banks (BSI) in Bukittinggi City - Afriadi, Ilham; Iznuddin, Iiz (Inovbiz: Jurnal Inovasi Bisnis, 2023)
BSI's challenge is certainly not as easy as imagined. In some studies, it is explained that the awareness of the Indonesian people is still very minimal about Islamic Banking products. The purpose of the study was to determine perceptions, the impact of mergers, and factors that can influence customer perceptions of the merger of three Islamic banks into Bank Syariah Indonesia in Bukittinggi City.The method used in the research is a qualitative method with a literature study approach (library research). The research was conducted in the city of Bukittinggi The data used in this study are two, namely primary data and secondary data accessed via the Web and Informants, namely post-merger BSI customers. Data analysis techniques with Display, Reduction, Verification, and Conclusion Drawing.Research results: (1) Customer perceptions of the merger of three Islamic banks into Bank Syariah Indonesia in Bukittinggi City, gave rise to two perceptions of customers Each customer must have a different point of view in responding to the changes that occur. Because with the merger of three Islamic banks into Bank Syariah Indonesia, it will bring changes both in management and the Islamic banking system used. (2) The impact of the merger of three Islamic banks into Bank Syariah Indonesia (BSI) on customer trust and loyalty. The results of the merger of the three Islamic banks are also in line with the government's efforts to create a halal economic ecosystem. Islamic banks will be an important pillar in the success of Islamic financial integration in Indonesia. Many conventional banks have supported the halal industry because of its wider reach and the flexibility of the products offered and can improve the efficiency of financial performance by being able to compete in the financial industry in Indonesia. (3) Factors that can affect the level of trust and loyalty of Indonesian Islamic bank customers in the city of bukittinggi, namely Service Quality provided by Bank Syariah Indonesia to customers, Tangibles (direct evidence / tangible), Reliability dimensions, Perceptiveness dimensions (responsiveness), Assurance dimensions (assurance), Empathy dimensions (empathy). As well as the level of convenience, security and transaction systems that are able to adjust to the level of community life needs in following technological developments. So with the merger carried out by three banks in Indonesia, it has a positive impact and has the ability to increase trust and loyalty for customers of Islamic banking cities in the city of Bukittinggi.